Current advances in produced water treatment technologies: a perspective of techno-economic analysis and life cycle assessment - Gangwar A.; Rawat S.; Rautela A.; Yadav I.; Singh A.; Kumar S. (My University, 2025)
The enhanced oil and gas exploration co-produces produced water (PW) as the largest waste stream, which contains higher concentrations of hydrocarbons, dissolved salts, heavy metals and chemical additives. The treatment of PW is crucial for water reuse for economic viability and long-term sustainability of oil and gas industries. In this aspect, the present study reviewed PW composition and different treatment technologies including hydrocyclone, membrane, mechanical vapor compressor, membrane desalination and biological and chemical precipitation. Further, advanced treatment processes such as Fenton process, electrocoagulation and ozone treatment are analyzed as effective ways to remove specific inorganic and organic pollutants. Relevant studies on techno-economic analysis (TEA) and life cycle assessment (LCA) have been explored comprehensively to address the sustainability and readiness of treatment technologies. The findings of this study underscore the necessity of combining two or more treatment strategies to establish commercially viable and environmentally sustainable PW treatment processes. The simultaneous TEA and LCA performance is advised to assess the technical, economic and environmental performance of novel PW treatment technologies. In this regard, the present study provides a road map to establish efficient PW treatment technologies to maximize economic benefits with minimum environmental burden. © The Author(s), under exclusive licence to Springer Nature B.V. 2024.